Untreated and under-treated depressive symptoms in people with multiple sclerosis in an Australian context: A secondary analysis. Issue 1 (February 2021) - Grech, Lisa B.; Haines, Sarah; Marck, Claudia H.; Hester, Robert; Butler, Ernest
Abstract: Background: The lifetime prevalence of depression in people with multiple sclerosis (MS) is ∼50% and international studies have reported untreated and under-treated depressive symptoms in this population. Aim: We aimed to identify whether this translates to an Australian context requiring attention by Australian healthcare services. Methods: We undertook secondary analysis of two studies totalling 217 participants (Study 1: N = 107; Study 2: N = 110) with relapsing remitting or secondary progressive MS, recruited from two hospital outpatient MS clinics and via email advertisement through MS Limited. Depressive symptoms were measured using the Beck Depression Inventory-Second Edition (BDI-II; Study 1), Patient Health Questionnaire – Nine (PHQ-9) and Center for Epidemiological Studies Depression-Revised (CESD-R; Study 2). Findings: In study 1, 11.9% of participants not taking antidepressant medication and 25.0% who were taking antidepressant medication reported moderate-to-severe depressive symptoms. In study 2, 21.0% and 23.5% of participants not taking antidepressant medication, while 37.9% and 55.1% taking antidepressant medication, reported moderate-to-severe depressive symptoms, measured by the PHQ-9 and CESD-R, respectively. Across both studies, people with MS taking antidepressant medication reported higher severity of depressive symptoms compared to those not taking antidepressant medication. Conclusion: These findings indicate untreated and undertreated depressive symptoms within an Australian context, highlighting the important role of nurses to educate people with MS about depressive symptoms, as well as to undertake symptom screening and monitoring. Further research is required to verify the extent of the issue and identify barriers to detection and treatment of depressive symptoms in Australians living with MS.